3
$\begingroup$

$$\int \frac{\sqrt{4x^2-8x+3}}{x-1}dx$$

What I first did is I tried to complete the square for the numerator

$\sqrt{4(x^2-2x+3/4)} = \sqrt{4(x^2-2x+1-1/4)} = \sqrt{4(x-1)^2 - 1}$

Now I did trig-substitution:

$(x-1) = \frac{1}{2}\sec(\theta)$

$dx = \frac{1}{2}\sec(\theta)\tan(\theta)d\theta$

$$=\int \frac{\tan^2(\theta)\sec(\theta)}{\frac{1}{2}\sec(\theta) }d\theta = 2\tan(\theta) - 2\theta + C = 2\frac{\sqrt{4x^2-8x+3}}{2} - 2\sec^{-1}\left(\frac{x-1}{2}\right) + C$$

$\endgroup$
  • $\begingroup$ You made a good attempt. Then why not continue by assuming $x-1=u$? $\endgroup$ – Juniven Apr 17 '17 at 6:43
  • $\begingroup$ ohhhhhhhhhhhhh not use that thx i get it $\endgroup$ – Tinler Apr 17 '17 at 6:44
  • $\begingroup$ Then the integral becomes $$\int\frac{\sqrt{4u^2-1}}{u}du$$ $\endgroup$ – Juniven Apr 17 '17 at 6:44
  • $\begingroup$ Like that? I edited $\endgroup$ – Tinler Apr 17 '17 at 6:47
  • 1
    $\begingroup$ set $t=2\cosh(y)$ $\endgroup$ – Dr. Sonnhard Graubner Apr 17 '17 at 6:51
1
$\begingroup$

If you substitute $u=\sqrt{4x^2-8x+3}$ you obtain $du=\dfrac{8x-8}{2\sqrt{4x^2-8x+3}}dx$. So : $$\int \frac{\sqrt{4x^2-8x+3}}{x-1}dx={\displaystyle\int}\dfrac{u^2}{u^2+1}\,du$$

Perform long division and you can finish easily.

$\endgroup$
0
$\begingroup$

I think your last step is wrong.

$2\tan\theta - 2\theta + c$

$= 2 \sqrt {\sec^2 \theta - 1} - 2 \theta + c$

As we have,

$\sec \theta = 2(x - 1)$

$\theta = \sec^{-1}2(x - 1)$

Put these values above,

$= 2 \sqrt {4x^2-8x+3} - 2 \sec^{-1}2(x - 1)+ c$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.